Golgi phosphoprotein 3 triggers signal-mediated incorporation of glycosyltransferases into coatomer-coated (COPI) vesicles - Eckert, Elias Simon Peter; Reckmann, Ingeborg; Hellwig, Andrea; Röhling, Simone; El-Battari, Assou; Wieland, Felix T.; Popoff, Vincent (The journal of biological chemistry, 2014)
Newly synthesized membrane and secreted proteins undergo a series of posttranslational modifications in the Golgi apparatus, including attachment of carbohydrate moieties. The final structure of so-formed glycans is determined by the order of execution of the different glycosylation steps, which seems intimately related to the spatial distribution of glycosyltransferases and glycosyl hydrolases within the Golgi apparatus. How cells achieve an accurate localization of these enzymes is not completely understood but might involve dynamic processes such as coatomer-coated (COPI) vesicle-mediated trafficking. In yeast, this transport is likely to be regulated by vacuolar protein sorting 74 (Vps74p), a peripheral Golgi protein able to interact with COPI coat as well as with a binding motif present in the cytosolic tails of some mannosyltransferases. Recently, Golgi phosphoprotein 3 (GOLPH3), the mammalian homolog of Vps74, has been shown to control the Golgi localization of core 2 N-acetylglucosamine-transferase 1. Here, we highlight a role of GOLPH3 in the spatial localization of α-2,6-sialyltransferase 1. We show, for the first time, that GOLPH3 supports incorporation of both core 2 N-acetylglucosamine-transferase 1 and α-2,6-sialyltransferase 1 into COPI vesicles. Depletion of GOLPH3 altered the subcellular localization of these enzymes. In contrast, galactosyltransferase, an enzyme that does not interact with GOLPH3, was neither incorporated into COPI vesicles nor was dependent on GOLPH3 for proper localization.